Similarities and Differences in the Glycosylation Mechanisms in Prokaryotes and Eukaryotes. (27th January 2011) - Dell, Anne; Galadari, Alaa; Sastre, Federico; Hitchen, Paul
Abstract : Recent years have witnessed a rapid growth in the number and diversity of prokaryotic proteins shown to carry N- and/or O-glycans, with protein glycosylation now considered as fundamental to the biology of these organisms as it is in eukaryotic systems. This article overviews the major glycosylation pathways that are known to exist in eukarya, bacteria and archaea. These are (i) oligosaccharyltransferase (OST)-mediated N-glycosylation which is abundant in eukarya and archaea, but is restricted to a limited range of bacteria; (ii) stepwise cytoplasmic N-glycosylation that has so far only been confirmed in the bacterial domain; (iii) OST-mediated O-glycosylation which appears to be characteristic of bacteria; and (iv) stepwise O-glycosylation which is common in eukarya and bacteria. A key aim of the review is to integrate information from the three domains of life in order to highlight commonalities in glycosylation processes. We show how the OST-mediated N- and O-glycosylation pathways share cytoplasmic assembly of lipid-linked oligosaccharides, flipping across the ER/periplasmic/cytoplasmic membranes, and transferring " en bloc " to the protein acceptor. Moreover these hallmarks are mirrored in lipopolysaccharide biosynthesis. Like in eukaryotes, stepwise O-glycosylation occurs on diverse bacterial proteins including flagellins, adhesins, autotransporters and lipoproteins, with O-glycosylation chain extension often coupled with secretory mechanisms.